2020
DOI: 10.3390/su12176799
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of CSR and Financial Distress on Financial Performance—Evidence from Chinese Listed Companies of the Manufacturing Industry

Abstract: This paper explores the impact of corporate social responsibility (CSR) and financial distress on corporate financial performance (CFP) in Chinese listed companies of the manufacturing industry. Covering a total of 1445 manufacturing observations from 2013 to 2018 by matching the China Stock Market & Accounting Research Database (CSMAR) and Ranking CSR Ratings (RKS) database and regression models, we find that CSR has a significant positive impact on CFP, and the relationship is more pronounced for firms t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
53
1
8

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 73 publications
(65 citation statements)
references
References 53 publications
3
53
1
8
Order By: Relevance
“…Based on the results of the statistical t-test it can be concluded that the variable of corporate social responsibility disclosure has a positive and significant influence on the CED. This study is in line with the study by [12] and [30], [31], [32], [33] whereby, based on "stakeholder theory," companies will voluntarily choose to disclose information about environmental and social performance. The more CSR disclosures there are, the more the company will reveal the amount of carbon emission.…”
Section: E Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…Based on the results of the statistical t-test it can be concluded that the variable of corporate social responsibility disclosure has a positive and significant influence on the CED. This study is in line with the study by [12] and [30], [31], [32], [33] whereby, based on "stakeholder theory," companies will voluntarily choose to disclose information about environmental and social performance. The more CSR disclosures there are, the more the company will reveal the amount of carbon emission.…”
Section: E Discussionsupporting
confidence: 84%
“…The more CSR disclosures disclosed by the company, the higher the disclosure of carbon emissions made by the company. Research conducted by [12] and [30], [31], [32], [33] shows that CSR positively affects carbon emission disclosure. Based on the description above, the following hypothesis can be formulated:…”
Section: Hypothesis Developmentmentioning
confidence: 99%
“…The firms with higher level of CSR enjoy more sales with less advertising expenses, which contribute in overall growth of the firm. Kapoor and Sandhu (2010) and Wu et al (2020) do not find any significant relationship between growth and CSR, which probably negatively influences the investors' decision of spending in firms. According to this, we state the following hypothesis:…”
Section: Corporate Social Responsibility and Growth Measuresmentioning
confidence: 78%
“…Abilasha and Tyagi (2019) revealed that better FP may lead to improved CSP and also better CSP may lead to improved FP, ceteris paribus. Wu et al (2020) found a significant positive relationship between CSR and FP of stable firms as corporate stability enhances the role of CSR in endorsing CFP. Proper attention of a company for the social well-being of its locality may positively lead to generate more returns to it in terms of profits (Nnenna and Carol, 2016).…”
Section: Literature Reviewmentioning
confidence: 86%
See 1 more Smart Citation